2012
DOI: 10.1063/1.4742065
|View full text |Cite
|
Sign up to set email alerts
|

Structures and magnetic properties of CrSin− (n = 3–12) clusters: Photoelectron spectroscopy and density functional calculations

Abstract: Chromium-doped silicon clusters, CrSi(n)(-) (n = 3-12), were investigated with anion photoelectron spectroscopy and density functional theory calculations. The combination of experimental measurement and theoretical calculations reveals that the onset of endohedral structure in CrSi(n)(-) clusters occurs at n = 10 and the magnetic properties of the CrSi(n)(-) clusters are correlated to their geometric structures. The most stable isomers of CrSi(n)(-) from n = 3 to 9 have exohedral structures with magnetic mome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 62 publications
7
51
0
Order By: Relevance
“…For the neutral CoGe n clusters, the total magnetic moments are 3 m B for n = 2, 3, 7, and 9, and 1 m B for n = 4, 5, 6, 8, 10, and 11. For both anionic and neutral CoGe n clusters, the magnetic moments decreased to the lowest values at n = 10 and 11, and this tendency is in agreement with previous DFT calculations on CoGe n [12,19] and the investigation into Si n Co (n = 10-12) clusters conducted by Li et al [39] The minimization of the magnetic moments at n = 10 and 11 is also in agreement with the formation of endohedral structures in CoGe n clusters and is consistent with the results for the CrSi n À (n = 3-12) clusters reported by Kong et al [40] From Table 3, we can see that the total magnetic moments are mainly contributed to by the cobalt atom because the local magnetic moments on the cobalt atom are close to the total magnetic moments in general. The minimization of the magnetic moments for these clusters can be ascribed to charge transfer from the germanium atoms to cobalt atom and strong spd hybridizations of the cobalt atom.…”
Section: Discussionsupporting
confidence: 92%
“…For the neutral CoGe n clusters, the total magnetic moments are 3 m B for n = 2, 3, 7, and 9, and 1 m B for n = 4, 5, 6, 8, 10, and 11. For both anionic and neutral CoGe n clusters, the magnetic moments decreased to the lowest values at n = 10 and 11, and this tendency is in agreement with previous DFT calculations on CoGe n [12,19] and the investigation into Si n Co (n = 10-12) clusters conducted by Li et al [39] The minimization of the magnetic moments at n = 10 and 11 is also in agreement with the formation of endohedral structures in CoGe n clusters and is consistent with the results for the CrSi n À (n = 3-12) clusters reported by Kong et al [40] From Table 3, we can see that the total magnetic moments are mainly contributed to by the cobalt atom because the local magnetic moments on the cobalt atom are close to the total magnetic moments in general. The minimization of the magnetic moments for these clusters can be ascribed to charge transfer from the germanium atoms to cobalt atom and strong spd hybridizations of the cobalt atom.…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, the transition metal (TM) atom-doped silicon clusters have attracted extensive attentions because these clusters show a variety of structural and electronic properties and tend to form closed-shell electronic structures. Much of the excitement in this field originates from the fact that TM atoms possess unfilled d orbital, their electronic structure and chemical properties depend upon the interplay between s and d electrons and can strongly influence the properties of silicon cluster [8][9][10][11]. Moreover, various promising potential applications of materials with novel properties based on TM@Si n clusters and TM-doped fullerenes are of significant importance to the silicon-based semiconductor fields such as surface film, catalysis, power source materials, data storage, magnetic resonance, and optical materials.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Different from carbon clusters that usually show sp 2 hybridization, bonding in pure silicon clusters occurs through sp 3 hybridization and thus they are more chemically reactive due to the existence of unsaturated dangling bonds on the clusters' surface, making them less suitable as nanoscale building blocks. 13 However, it has been found that silicon clusters can be stabilized by doping with transition metal (TM) atoms, [14][15][16] and by now a great number of studies, both experimentally [17][18][19][20][21][22][23][24][25][26][27][28][29] and theoretically, [30][31][32][33][34][35][36] have explored the structures and electronic properties of TM-doped silicon clusters for their potential use in silicon-based nanomaterials. In fact, doping silicon clusters with appropriate transition metal atoms [37][38][39][40][41] can reduce the number of dangling bonds on the cluster surface or even fully saturate them via pd hybridization, and thereby change the geometrical structures and chemical reactivities compared to pure silicon clusters.…”
Section: Introductionmentioning
confidence: 99%